Characterization of mouse models of Mycobacterium avium complex infection and evaluation of drug combinations - Andréjak, Claire; Almeida, Deepak V; Tyagi, Sandeep; Converse, Paul J; Ammerman, Nicole C; Grosset, Jacques H (Antimicrobial agents and chemotherapy, 2015)
The Mycobacterium avium complex is the most common cause of nontuberculous mycobacterial lung disease worldwide; yet, an optimal treatment regimen for M. avium complex infection has not been established. Clarithromycin is accepted as the cornerstone drug for treatment of M. avium lung disease; however, good model systems, especially animal models, are needed to evaluate the most effective companion drugs. We performed a series of experiments to evaluate and use different mouse models (comparing BALB/c, C57BL/6, nude, and beige mice) of M. avium infection and to assess the anti-M. avium activity of single and combination drug regimens, in vitro, ex vivo, and in mice. In vitro, clarithromycin and moxifloxacin were most active against M. avium, and no antagonism was observed between these two drugs. Nude mice were more susceptible to M. avium infection than the other mouse strains tested, but the impact of treatment was most clearly seen in M. avium-infected BALB/c mice. The combination of clarithromycin-ethambutol-rifampin was more effective in all infected mice than moxifloxacin-ethambutol-rifampin; the addition of moxifloxacin to the clarithromycin-containing regimen did not increase treatment efficacy. Clarithromycin-containing regimens are the most effective for M. avium infection; substitution of moxifloxacin for clarithromycin had a negative impact on treatment efficacy.